Coherence between discourses and practices of sustainability in the pharmaceutical multinational companies in Brazil - Salomão, Devani (Seven Editora, 2023)
Through documental and field research, this study aims to verify the attributed interpretation of managers and her/his direct employees of the sustainability term; investigate and analyze if there are contradictions between the organization's speech and the management practice inside the sphere of communication and sustainable management. As for the approach, it used quantitative and qualitative methods. As for the goal, the exploratory procedure was implemented. The instrument for data gathering was two questionnaires, one for managers and one for the respective employees of these managers. The goals and objectives of the industries appear to be, by the answers, common knowledge. The individual and organizational goals, although diverse, are all aligned with the ends they want to reach. Our hypothesis seems not to be ratified, but the overall goal is. It is inferred that there is no contradiction between managerial discourse and practices, existing on the part of employees' and managers' understanding of what it is to have sustainable attitudes.DOI: https://doi.org/10.56238/devopinterscie-007